Time is tissue. Want to save millions in wound care? Start early: a QI project to expedite referral of high-risk wound care patients to specialised care - John Muen Hwang (BMJ Open Quality)
Introduction Wound care is a multibillion-dollar industry, and most research and treatment are geared towards late-stage or end-stage care. The longer a patient has a wound, the more likely it is that complications (like sepsis or vascular compromise) will occur that will both extend treatment and multiply costs. We postulated that much of the suffering and healthcare costs of chronic wounds could be avoided by early identification of high-risk patients and subsequent earlier intervention. In an established regional wound clinic, our aim was to decrease referral times by 50% within 1 year, and to demonstrate the beneficial outcomes on wound healing and total cost of care.Methods A prospective interventional quality improvement study was performed between June 2017 and June 2018. We determined baseline referral times to the clinic and then performed three interventions. The effects on referral time, healing time and number of home care visits to achieve wound healing were collected and displayed on annotated control charts. The cost of care and potential for cost avoidance was determined by an analysis of the medical encounters of twenty chronic wound patients.Results We achieved a 53.6% reduction in average referral times to the clinic, a 59.6% reduction in average healing times and a 66.0% reduction in the average number of home care visits required to achieve healing. Our cost analysis suggested the potential for significant cost avoidance (87.7%) compared with delayed treatment outside the clinic.Conclusions Early identification and treatment of patients at high risk for wound chronicity and complications, followed by early referral to and treatment at a specialised wound clinic, resulted in faster healing and reduced health system costs.